Patricia Lacks' contributions to evidence-based practice for insomnia - Kay, Daniel B.; Wolfson, Amy R. (Frontiers in Sleep, 2023)
In the 1980s, Patricia Lacks (Feb. 22, 1941 – Dec. 3, 2016) began a systematic program of research at Washington University in St. Louis to identify the causes of insomnia and effective treatments. Her treatment outcomes research culminated in the publication of the first detailed cognitive-behavioral treatment manual for insomnia, Behavioral Treatment for Persistent Insomnia. This paper focuses on the history of Dr. Lacks and her contributions to the field of insomnia research and practice.